2008
DOI: 10.1007/s11211-008-0069-9
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Analysis of the Vulnerability, Disorder, and Social Integration Models of Fear of Crime

Abstract: The current research tests three conceptual models designed to explain citizens' fear of crime-vulnerability, disorder, and social integration. These models are assessed for differential impact across the cognitive and affective dimensions of fear of crime. The analysis reported here considers the consecutive and simultaneous influence of individual-and city-level factors using multilevel modeling techniques. Recently collected survey data for 2,599 citizens nested within 21 cities across Washington State prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
217
1
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(243 citation statements)
references
References 57 publications
16
217
1
9
Order By: Relevance
“…For the ecological predictors, our results were partially consistent with those in the literature (Franklin et al 2008;Skogan 1995;Taylor and Covington 1993). Indeed, we showed perceived risk at the local level to be increased by the crime rate and by unemployment rate.…”
Section: Discussionsupporting
confidence: 91%
“…For the ecological predictors, our results were partially consistent with those in the literature (Franklin et al 2008;Skogan 1995;Taylor and Covington 1993). Indeed, we showed perceived risk at the local level to be increased by the crime rate and by unemployment rate.…”
Section: Discussionsupporting
confidence: 91%
“…McGarrell et al (1997) found that perceived disorder is a powerful predictor of fear on both an individual and a neighborhood level; and in Great Britain, Hope and Hough (1988) reported a strong relationship between disorder and fear, even after controlling for other aspects of community life. Franklin et al (2008) conducted a multilevel study of fear of crime in 21 cities in Washington and found that disorder explained the most variation in fear (Franklin et al 2008). The nature of the relationship between disorder and fear may vary depending on whether the level of analysis is conducted at the individual-or neighborhood-level (McGarrell et al 1997;Wyant 2008).…”
Section: Disorder and Prior Victimizationmentioning
confidence: 99%
“…In addition, survey research has documented racial differences in levels of fear of crime, with Blacks and other racial and ethnic minorities indicating greater fear than Whites (e.g., Baumer 1978;Covington and Taylor 1991;Pantazis 2000;Thompson et al 1992; but see also Ortega and Myles 1987). Scholars have suggested several possible reasons for why women and minorities demonstrate greater levels of fear of crime (for a review see Franklin et al 2008). For example, the vulnerability model suggests that women, the elderly, racial minorities and those living in poverty feel more vulnerable to crime because they perceive themselves as either less physically or financially capable of protecting themselves and their possessions than dominant groups (see Hale 1996 for a review).…”
Section: Demographic Differences In the Link Between Fear Of Crime Anmentioning
confidence: 99%